AB0143 Uncontrolled Expression of S100A8 Homodimers in the Absence of S100A9 Exacerbates TNFα-Mediated Psoriatic-Like Arthritis. (9th June 2015) - Thurainayagam, S.; Wixler, V.; Hermann, S.; Roth, J.; Vogl, T.
Abstract : Background: Psoriasis is a chronic autoimmune disorder frequently associated with arthritis (PsA). Alarmins S100A8 (myeloid related protein, MRP8) and S100A9 (MRP14), expressed in granulocytes, monocytes and activated keratinocytes, are highly up-regulated in psoriatic skin and synovium. Analysis of mice that are deficient for S100A9 demonstrated a pivotal role of these proteins for many inflammatory diseases (1). Notably, although S100a8 mRNA remains unchanged in S100A9-deficient (S100A9-/-) mice, S100A8 protein expression is abrogated, thus generating a functionally double knockout mouse model (3). Moreover, these mice show reduced inflammatory activities in several mouse models of infection and inflammation. Recently we generated doxycycline-inducible human TNFa–transgenic mice (ihTNFtg) which display the major features of inflammatory arthritis with fore paws being prominently affected (2). Objectives: To investigate the role of S100A8/S100A9 on the disease progression during TNFα-mediated psoriatic-like arthritis. Methods: hTNFα was induced in ihTNFtgxS100A9-/- mice by doxycycline and alterations of body weight, paw swelling and grip strength were examined compared to ihTNFtg mice. In addition, 18 F-FDG whole body PET scans were performed to quantify inflammation in these mice. S100A8 expression was analysed in various organs, skin, BMC and blood cells by IHC, Western blotting and FRI. Results: Unexpectedly, we observed an enhanced disease progression in ihTNFtgxS100A9-/- mice as loss of body weight and grip strength, increased paw swelling and cartilage destruction compared to ihTNFtg mice. Moreover, 18 F-FDG-PET imaging also illustrated an increased inflammatory activity mainly in DIP joints and organ impairment. Interestingly, we clearly saw a re-expression of pro-inflammatory S100A8 protein in bone marrow, blood, skin and nail keratinocytes. Conclusions: We hypothesize that in the absence of its binding partner S100A9, constitutively active S100A8 homodimers aggravate TNFα-mediated psoriatic-like arthritis. Our data indicate a complex S100A8/S100A9 regulatory mechanism of an alarmin-driven inflammation. References: Vogl, T. et al. Mrp8 and Mrp14 are endogenous activators of Toll-like receptor 4, promoting lethal, endotoxin-induced shock. Nat Med 13, 1042-1049 (2007). Retser, E. et al. Doxycycline-induced expression of transgenic human tumor necrosis factor alpha in adult mice results in psoriasis-like arthritis. Arthritis Rheum 65, 2290-2300 (2013). Manitz, M. P. et al. Loss of S100A9 (MRP14) results in reduced interleukin-8-induced CD11b surface expression, a polarized microfilament system, and diminished responsiveness to chemoattractants in vitro. Mol Cell Biol 23, 1034-1043 (2003). Disclosure of Interest: None declared